OGC O04 A Preoperative Scoring Model to Estimate the Risk of Conduit Necrosis in Oesophagectomy Patients - Results From the Oesophago-Gastric Anastomosis Audit. (7th December 2022) - Halle-Smith, James; Kamarajah, Sivesh; Evans, Richard; Griffiths, Ewen
Abstract: Background: Both conduit necrosis (CN) and anastomotic leak (AL) after oesophagectomy is associated with high morbidity and mortality and therefore identification of preoperative, modifiable risk factors are desirable. Once identified, risk factors can be used to create a risk scoring model which can be used to aid preoperative counselling and guide postoperative management. The aim of this study was to use the prospectively collected, multicentre data from the Oesophago-Gastric Anastomosis Audit (OGAA) to generate a risk scoring model for conduit necrosis and anastomotic leak after oesophagectomy. Methods: This prospective multicentre cohort study included patients undergoing oesophagectomy for oesophageal cancer between April 2018 and December 2018 (with 90 days of follow-up). Definitions for AL and CN were those set out by the Esophageal Complications Consensus Group. Univariate and multivariate analyses were performed to identify risk factors for both AL and CN. The cohort was then randomly split into a derivation an validation set. A risk score was then produced for both AL and CN using the derivation set, then internally validated using the validation set. Results: This study included 2247 oesophagectomies across 137 hospitals in 41 countries. The AL rate was 14.2% (n = 319) and CN rate was 2.7% (n = 60). Preoperative factors that were independent predictors of CN were: body mass index (BMI), Eastern Cooperative Oncology Group (ECOG) performance status, previous myocardial infarction (MI) and smoking history. These were converted into a risk-scoring model and internally validated using the validation set with an area under the receiver operating characteristic curve (AUROC) of 0.775. Preoperative factors that were independent predictors of AL were cardiovascular comorbidity (previous MI, peripheral vascular disease, previous stroke) and chronic obstructive pulmonary disease (COPD). This was converted to a risk scoring model but when internally validated the AUROC showed insufficient predictive ability (0.618). Conclusions: The present risk scoring model provides an internally validated tool to estimate a patient's risk of CN preoperatively. This could be used to inform preoperative counselling and guide postoperative management. External validation is required to further assess the predictive ability of this score. Despite a large dataset, AL proves difficult to predict using preoperative factors.